Efecto de factores ambientales, de la nutrición nitrogenada y su interacción sobre el rendimiento y el contenido de proteína de trigo Triticum aestivum (L.) en el centro de la Provincia de Santa Fe - Pérez, Diego Hugo (2020)
Available information regarding nitrogen foliar fertilization in wheat in Santa Fe province in Argentina is limited. The aims of the present thesis were: 1) quantify the response of grain yield to nitrogen fertilization based on environmental predictors such as water availability and photothermal quotient, 2) to quantify the effect of nitrogen fertilization on grain protein content as related to temperature and water availability effects during grain filling and 3) to study the role of foliar applications on wheat productivity and protein content. Data was obtained from fifteen N fertilization experiments, conducted in 2015 and 2016 growing seasons. Treatments consisted on six levels of applied N: 0, 40, 80, 120, 160 y 200 kg applied N ha -1 , each level with and without foliar fertilization in pre-flowering stage. Data was analyzed using no-linear mixed effect models. Yield increases with N fertilization were evident in most trials, but the response depended on the specific site. Yield response was explained by soil N availability at sowing and photothermal coefficient during September. Protein response was explained by sowing date, organic matter and photothermal coefficient of September.